Federal constitution: determining the level of awareness and knowledge among Malay student leaders of UiTM Cawangan Pahang / Hazlin Hasan … [et al.] - Hasan, Hazlin; Md Pauzi, Suria Fadhillah; Mustapha, Musramaini; Ghazali, Mohd Samsuri; Syed Hamid, Sharifah Shatrah (2015)
In Malaysia, there is a written constitution which states that the Federal Constitution is the supreme law of the land. It is the most vital document in any State as it serves as a social contract between the State and its people. It states the rights and status of the Malay Rulers, the prerogatives of the Malays and Bumiputeras and Bahasa Melayu as the national language amongst others. The history of how Malaysia achieves its independence has shaped the uniqueness of the Constitution. However, with the many controversial issues being debated today among youths in the social media, it is very pertinent for the youth especially the young Malay leaders to really appreciate its importance so as not to be manipulated by irresponsible parties. Therefore, the researchers found it is important to gauge the level of awareness and knowledge of these youth on Federal Constitution as the findings of the study would be useful in suggesting appropriate programs that can be conducted by UiTM Cawangan Pahang in enhancing their student leaders' awareness and knowledge on this fundamental law. This paper analysed the awareness and the level of knowledge of student leaders in UiTM Cawangan Pahang on the basic rights found in the Federal Constitution. A total of 81 Malay student leaders were conveniently selected to participate in this study. The data were analysed using SPSS Version 21.0 software programme. Descriptive statistics was used to analyse the data which included frequencies, mean and standard deviation. The study concluded that even though the level of awareness and the level of knowledge of the respondents were quite high, they still need to be exposed to a more comprehensive program that could help them understand better their rights as a citizen of Malaysia, thus preparing them to be knowledgeable future leaders of Malaysia.